Keparahan Penyakit Tungro dan Preferensi Wereng Hijau terhadap Berbagai Dosis Pemupukan Nitrogen - Achmad Gunawan; Purwono Purwono; Iskandar Lubis; I Nyoman Widiarta (Institut Pertanian Bogor, 2024)
The severity of disease symptoms is affected by triangular interactions between pathogens, hosts, and the environment. This study aims to describe the severity of tungro disease symptoms concerning the resistance of rice varieties and various fertilization rates. The research used the potting method in the Center for Rice Research, Sukamandi greenhouse. The experiment was designed using a Randomized Design, with 3 varieties: Ciherang (sensitive), IR 64 (green leafhopper resistance), and Inpari 36 Lanrang (virus resistance) as the main plot, and 4 levels of combination fertilization: (1) compound fertilizer + without urea; (2) compound fertilizer and urea 250 kg/ha; (3) compound fertilizer and urea 350 kg/ha; and (4) compound fertilizer and urea 500 kg/ha, as subplots. The data was processed using Anova and Duncan's multiple distance test. The results showed that rice variety significantly affected vector preference and the severity of tungro symptoms. The dose of nitrogen fertilization does not give different results to the preferences of insects and the severity of tungro in the greenhouse. There is no interaction between the variety and the dose of fertilizing. Resistant varieties are less preferred by green leafhoppers than the sensitive varieties. Keywords: antixenosis, Nephotettix virescens nitrogen fertilizer, preference